The development of Political Science in Argentina - Bulcourf, Pablo Alberto (Política. Revista de Ciencia Política, 2012)
This paper analyzes the development of political science in Argentina taking into account the social, political, cultural and economic processes in which the discipline developed during the twentieth century. Analytically, this paper emphasizes actors, scientific-academic products, teaching and research institutions, and networks. The process of institutionalization and professionalization initiated in the eighties is studied based on the conformation of disciplinary areas, including: State, administration and public policy; institutions, political processes and comparative politics, and international relations.